Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s12144-022-03795-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of balanced time perspective mediating the relationship between mindfulness as a trait and life satisfaction in Catalan University students

Abstract: The objective of the present study was to replicate previous studies by examining the potential connections between mindfulness as a trait, life satisfaction and time perspectives (TP) and to analyze if balanced time perspective (BTP) could act as a possible mediator between mindfulness and life satisfaction in students from the University of Girona (Catalonia, Spain). Data was collected from 341 Catalan university students aged 18–52 (77.1% women; mean age = 23.62) who completed Zimbardo Time Perspective Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Recent studies exploring the mediating roles of balanced time perspective (Ballabrera & Burriel, 2022), savoring positive experiences, and gratitude (Cheung & Lau, 2021) further expand the landscape of research on mindfulness and life satisfaction. Moreover, the investigation into the interplay among psychological need satisfaction, sleep, and mindfulness in specific populations such as those living with HIV (Campbell et al, 2016) highlights the diverse pathways through which mindfulness can impact life satisfaction and overall well-being.…”
Section: E-issn: 3041-8542mentioning
confidence: 99%
“…Recent studies exploring the mediating roles of balanced time perspective (Ballabrera & Burriel, 2022), savoring positive experiences, and gratitude (Cheung & Lau, 2021) further expand the landscape of research on mindfulness and life satisfaction. Moreover, the investigation into the interplay among psychological need satisfaction, sleep, and mindfulness in specific populations such as those living with HIV (Campbell et al, 2016) highlights the diverse pathways through which mindfulness can impact life satisfaction and overall well-being.…”
Section: E-issn: 3041-8542mentioning
confidence: 99%
“…For example, perceived well-being has been positively associated with a positive past orientation, a future orientation, and a balanced time profile, whereas it has been negatively related to past negative and present fatalistic orientations [36][37][38][39][40]. Similarly, mental health and satisfaction with life have been positively related to a balanced time perspective [41][42][43][44]. It has also been observed how a present-and future-oriented perspective is positively related to higher self-esteem, whereas a greater orientation to the past is associated with lower levels of self-esteem [45].…”
Section: Family Functioning and Time Perspectivementioning
confidence: 99%
“…Satisfaction with life has been identified as a primary component of subjective wellbeing, defined as a cognitive process and an individual's overall evaluation of one's life [1]. Current studies associate this component with people's mental and physical health [2][3][4][5]. For example, Lopes and Nihei [6] demonstrated that university students with higher life satisfaction developed more adaptive management of circumstances and psychological well-being during the COVID-19 pandemic, resulting in greater resistance to depressive and anxiety symptoms and stress.…”
Section: Introductionmentioning
confidence: 99%